Communicating the open access policy landscape - Chris Awre; Andrew Beeken; Bev Jones; Paul Stainthorp; Graham Stone (Insights: The UKSG Journal, 2016)
The HHuLOA (Hull, Huddersfield, Lincoln Open Access) project is a two-year Jisc-funded project, which seeks to identify how open access (OA) support mechanisms can be used to assist with the development of research. One such area is policy landscape, which has shifted dramatically in the past two years. Many academic staff have been left confused, frustrated and stressed by new obligations placed upon long-established publishing practices and by the way in which these changes have been communicated. This paper describes the project’s initial work undertaken in this area, with the aim of enabling academic audiences to better navigate the policy environment they find themselves in to comply and better understand the rights they have when using OA.